2019
DOI: 10.1080/13880209.2019.1649436
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of lutein on isoproterenol-induced cardiac failure rat model through improving cardiac morphology, antioxidant status via positively regulating Nrf2/HO-1 signalling pathway

Abstract: Context: Lutein (LU) is a major carotenoid with various pharmacological activities including anti-inflammatory, antioxidant and anti-apoptosis. Objective: The cardioprotective efficacy of LU was determined by evaluating the biochemical and histopathological changes in isoproterenol (ISO) induced myocardial infarction (MI) rat model. Materials and methods: Healthy male albino rats ( n = 40) were segregated into 4 equal groups. Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 28 publications
5
35
0
Order By: Relevance
“…Similarly, the infarct size was also significantly increased in ISP‐induced rats owing to increased myocardial damage (necrosis and apoptosis) and results in a lack of oxygen (hypoxia) and glucose (mitochondrial dysfunction). Similar kind of results was also observed in other studies (Khan et al., 2019; Ouyang et al., 2019). The cardiac infarct size (area) was markedly reduced in TAN administered rats due to cardio preservative activity through abolishing mitochondrial dysfunction and enhance myocardial degeneration (Lu et al., 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, the infarct size was also significantly increased in ISP‐induced rats owing to increased myocardial damage (necrosis and apoptosis) and results in a lack of oxygen (hypoxia) and glucose (mitochondrial dysfunction). Similar kind of results was also observed in other studies (Khan et al., 2019; Ouyang et al., 2019). The cardiac infarct size (area) was markedly reduced in TAN administered rats due to cardio preservative activity through abolishing mitochondrial dysfunction and enhance myocardial degeneration (Lu et al., 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Even though currently we have many treatment regimens to minimize the risk of MI and its related symptomatic condition but till date no effective remedies are available. Hence, many researchers are still working to find an effective cardioprotective agent that can lower the risk of MI (Heusch & Gersh, 2017; Ouyang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The biochemical and histopathological changes of lutein (40 mg/kg, p.o., for 28 days) against isoproterenol (ISO)-induced (85 mg/kg, s.c., for two consecutive days) myocardial infarction (MI) rat model was evaluated by Ouyang et al 38 . Their results suggested that pretreatment with lutein "significantly reduced infarction size, lipid peroxidation product, cardiac markers [(lactate dehydrogenase (LDH), creatine kinase-MB (CK-MB) and cardiac troponin T (cTn T)], inflammatory markers (IL-1β, IL-6, TNF-α and NF-κB p65), and apoptotic markers (caspase-3 and -9)".…”
Section: Cardioprotective Activitymentioning
confidence: 99%
“…Their results suggested that pretreatment with lutein "significantly reduced infarction size, lipid peroxidation product, cardiac markers [(lactate dehydrogenase (LDH), creatine kinase-MB (CK-MB) and cardiac troponin T (cTn T)], inflammatory markers (IL-1β, IL-6, TNF-α and NF-κB p65), and apoptotic markers (caspase-3 and -9)". 38 In addition, lutein significantly increased antioxidant levels [catalase (CAT) and SOD] as well as dramatically upregulated HO-1 and Nrf-2 protein expressions. In addition, lutein significantly reversed all the histopathological changes and thus confirmed its cardioprotection.…”
Section: Cardioprotective Activitymentioning
confidence: 99%
See 1 more Smart Citation